2001
DOI: 10.1046/j.1440-1622.2001.02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal cyst: A changing pattern of presentation

Abstract: There is a changing trend in the commonest mode and age of presentation; fewer patients are presenting with the classical triad and the mean age of presentation is higher. Reconstruction by hepaticoduodenostomy is equally effective, more physiological and less time consuming as compared to hepaticojejunostomy, if the anastomosis can be achieved without tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In this and other series, pain was more common in adults, but this finding may be due to the fact that small children are unable to express this symptom. 1,8,13,21 Lipsett et al 8 from Johns Hopkins University found that adults were more likely to present with cholecystitis and pancreatitis, but this observation was not confirmed in this Wisconsin series. In addition, the finding that Wisconsin adults were more likely to present with cholangitis may be due to the fact that they had relatively more type IVA and V cysts and were more likely to have preoperative biliary stenting.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this and other series, pain was more common in adults, but this finding may be due to the fact that small children are unable to express this symptom. 1,8,13,21 Lipsett et al 8 from Johns Hopkins University found that adults were more likely to present with cholecystitis and pancreatitis, but this observation was not confirmed in this Wisconsin series. In addition, the finding that Wisconsin adults were more likely to present with cholangitis may be due to the fact that they had relatively more type IVA and V cysts and were more likely to have preoperative biliary stenting.…”
Section: Discussionmentioning
confidence: 59%
“…However, the overall distribution of cysts in this series, with types I and IVA being most common is similar to many other reports. 1,8,9,18,19,21 Once considered, the diagnosis of biliary cyst disease is easily established with modern imaging studies. Ultrasound has the advantages of imaging intrahepatic stones and avoiding radiation exposure but does not provide sufficient detail regarding vascular and pancreatobiliary duct anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Today, these malformations are most often classified according to the Todani modification of the Alonso‐Lej classification (Table 1). The classic type and most common (50%–60%) choledochal cyst is the type I, cystic (a), sacclar (b), or fusiform (c) dilatation of the extrahepatic biliary tree . Type II cysts are simple diverticula of the extrahepatic biliary tree and are extremely rare, accounting for fewer than 5% of all cysts.…”
Section: Classificationmentioning
confidence: 99%
“…The classic type and most common (50%-60%) choledochal cyst is the type I, cystic (a), sacclar (b), or fusiform (c) dilatation of the extrahepatic biliary tree. [2][3][4][5][6][7][8] Type II cysts are simple diverticula of the extrahepatic biliary tree and are extremely rare, accounting for fewer than 5% of all cysts. A choledochocele, or type III cyst, is a cystic dilatation of the intraduodenal portion of the extrahepatic portion of the biliary tree.…”
Section: Classificationmentioning
confidence: 99%
“…[67][68][69] However, MRCP has been shown to be just as good as 70,71 if not better than 70 ERCP, without the potential complications of the latter, invasive technique. 70 …”
Section: Endoscopic Retrograde Cholangiopancreatographymentioning
confidence: 99%